Techniques for responsible alcohol service [videorecording] - National Restaurant Association. The Educational Foundation (Lansing, Mich. National Restaurant Association, 1996)
This program discusses methods for monitoring a customer's level of intoxication and behavior change while comsuming beverage alcohol. Discusses the traffic light method used for communication among service staff.
VHS
Keywords: Alcoholic beverages; Bartenders; Bartending; Food service; Drinking of alcoholic beverages -- United States